2015
DOI: 10.20870/jph.2015.e003
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale mapping of sapwood anatomical properties reveals plasticity in hydraulics during water deficit

Abstract: <p style="text-align: justify;">Growth responses to water deficit translate into discernible changes in the structure of woody tissues and provide an integrated record of historical water availability throughout the life of the individual. The highly dynamic nature of woody growth can impart adaptive changes in physiological performance through changes in xylem elements that regulate water transport. Here, we present a case study of how sapwood anatomical properties can be mapped using point dendrometers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…On the other hand, traits that are phenotypically plastic can potentially compensate for mismatches between actual environmental conditions and the conditions to which the genetically controlled traits are adapted (Nicotra et al, 2010). Studies have shown that leaf morphological, physiological (Pita & Pardos, 2001;Corcuera et al, 2011;McLean et al, 2014;Johnson et al, 2018) and anatomical traits (Mitchell & Worledge, 2015) are phenotypically plastic and can adjust to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, traits that are phenotypically plastic can potentially compensate for mismatches between actual environmental conditions and the conditions to which the genetically controlled traits are adapted (Nicotra et al, 2010). Studies have shown that leaf morphological, physiological (Pita & Pardos, 2001;Corcuera et al, 2011;McLean et al, 2014;Johnson et al, 2018) and anatomical traits (Mitchell & Worledge, 2015) are phenotypically plastic and can adjust to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%